Blender 3D by example : design a complete workflow with Blender to create stunning 3D scenes and films step by step! /: design a complete workflow with Blender to create stunning 3D scenes and films step by step!. (2015) - Caudron, Romain; Nicq, Pierre-Armand
No abstract available